Family involvement in immigrants health care - Manuel Moreno Preciado (Universidad de Alicante, 2012)
The present study is an approach to health care in immigrants and their domestic environment, obtained by means of experience gathered in the latest years. In the use of social and cultural factors applied to processes of health/sickness/attention, the anthropological view has been of more help in some cases than others circumstance that can be confirmed in those cases related to cultural diversity: food habits, costume, language barriers, religious practices, controversial traditions... etc... At the same time some other interesting factors as social conditions within the immigrant context have been neglected. This sort of biased view offers an out of context analysis concealing the imminent social etiology of health problems in those immigrant communities as recently paramount studies have shown. Thus, a change of direction is needed, a direction that should focus the studies in the cross-road of two processes or ways: the immigrant process and the health/sickness/attention process. The strong cultural tendencies predominant in medical professionals could only be overcome when there be a special education to promote cultural diversity according to what Edgar Morin proposes, an education focussed in human condition.